Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1203/00006450-197901000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Parathormone and Perinatal Calcium Homeostasis

Abstract: Summawand Rudd (49) have observed mean PTH concentrations in cord Plasma measured the first parathormone (PTH) and calcium concentrations were in 309 specimens collected from 190 newborns during 7 days of life. The patient material consisted of 51 preterm, 130 term, and 9 postterm infants, including 22 infants of diabetic mothers (IDM), 38 infants with hypocalcemia, and 25 asphyxiated infants. PTH was detectable, although in low concentrations, in cord blood samples despite the presence of elevated calcium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…This hypothesis warrants further investigation once the molecular identity of the renal magnesium transporters has been described. The serum PTH concentration of 8-wk-old OD was lower than that of OC rats in the current study, which is in accordance with observations in human neonates (2,19,20). A number of hypotheses have been proposed to account for the apparent paradox of hypocalcemia and low PTH concentration.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This hypothesis warrants further investigation once the molecular identity of the renal magnesium transporters has been described. The serum PTH concentration of 8-wk-old OD was lower than that of OC rats in the current study, which is in accordance with observations in human neonates (2,19,20). A number of hypotheses have been proposed to account for the apparent paradox of hypocalcemia and low PTH concentration.…”
Section: Discussionsupporting
confidence: 80%
“…We assessed renal function in rats at 4 wk of age, before puberty, and at 8 wk of age, after puberty, to determine whether in utero exposure to maternal diabetes exerts a long-term programming effect on offspring kidney function. We also measured serum PTH concentration, as this has been reported to be lower in human offspring of diabetic pregnancy (2,19,20) and may contribute to altered renal calcium and magnesium handling.…”
mentioning
confidence: 99%
“…Human fetuses share the finding of an elevated serum calcium and ionized calcium, typically 0.30 -0.50 mM above the maternal level (143,148,463,523,594,595). This has been demonstrated at 15-20 wk of gestation by fetoscopy (453), and at delivery of preterm singleton and twin pregnancies (mean gestational age 33 wk) (152).…”
Section: Human Datamentioning
confidence: 99%
“…Moreover, biologically active PTH circulates in normal subjects at picomolar concentrations (6, 7), which, until recently, have been beyond the detectability of most assay systems. It is not surprising, then, that iPTH in fetal and umbilical cord blood has been reported as indeterminate or low in some series (5,(8)(9)(10)(11)(12)(13)(14) and normal, or even elevated, compared with maternal or other adult levels (4, 15-18) in others. A variety of iPTH levels have also been reported in association with early neonatal hypocalcemia (1, 3,12,19).…”
mentioning
confidence: 99%
“…It is not surprising, then, that iPTH in fetal and umbilical cord blood has been reported as indeterminate or low in some series (5,(8)(9)(10)(11)(12)(13)(14) and normal, or even elevated, compared with maternal or other adult levels (4, 15-18) in others. A variety of iPTH levels have also been reported in association with early neonatal hypocalcemia (1, 3,12,19).Using the ultrasensitive CBA for PTH developed by Chambers (20), Care et al (21,22) showed that bioPTH in porcine fetal plasma exceeds paired maternal plasma bioPTH. Similarly, Allgrove et al (14) reported that human term umbilical cord plasma bioPTH is elevated 5-to 6-fold above paired maternal plasma bioPTH and significantly exceeds values determined in normocalcemic adults.…”
mentioning
confidence: 99%